THE ROLE OF INTERNATIONAL ENERGY AGENCY IN THE DEVELOPING OF NEW AND RENEWABLE ENERGY IN INDONESIA - Nalurita, Humaira Salsabila; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
In the development of energy, International Energy Agency made Indonesia as a priority country. In particular, renewable energy is the mayor concern as an alternative energy replacing fossil fuels. Meanwhile, Indonesia has abundant renewable energy potentials which consist of geothermal, biomass, solar, wind, and water. Unfortunately, the utilization of these potentials was still far from maximal. Thus, renewable energies in Indonesia have caught the attention of International Energy Agency.This research aimed to understand the role of International Energy Agency to develop the new and renewable energies in Indonesia. According to liberalists’ perspective used in this research, it is argues that international organization has the task of providing information that can influence a relative gains. The theory used was international organization theory and the role theory where international energy was established as a forum to achieve goals and international organization has a place in the international community. The methods used was qualitative and used data from journals, books, documents, and websites.The result of this study revealed that International Energy Agency analyzes and assesses Indonesia’s energy policy and release its review. In that review, International Energy Agency gives some recommendations regarding the improvement of new and renewable energy policies. Some of those recommendations have been implemented by Indonesia while some of them are still in the process of execution. Keynote: energy policies, international energy agency, renewable energy